Machine Learning Methods for Feature Importance and Migration Prediction Related to Internal Migration by Province in Turkey - Öztürk, Meryem Pulat (İstanbul Üniversitesi, 2025)
In this study, the variables affecting internal migration on a provincial basis in Turkey between 2018 and 2022 were determined using feature importance, and migration estimates were made using machine learning algorithms. Incoming and outgoing migrations were considered separately. The main objective of the study is to determine in detail the factors that influence incoming and outgoing migration and to reveal which variables are more explanatory in the prediction process. In this regard, this study is one of the rare examples of a machine learning approach on internal migration in Turkey and provides original contributions to the field. In the study, the following features were taken that can be accessed on a provincial basis between 2018 and 2022 and are frequently used in the literature: number of academicians, number of hospitals, number of private hospitals, GDP, number of teachers, number of schools, agricultural areas, population density, population growth rate, probable duration of education, average duration of education, number of traffic accidents, number of automobiles, number of tractors, completed education status, import, export, number of physicians, number of hospital beds, and number of housing sales. In the R programme, the feature importance determination process was performed using the Caret package with various modelling techniques, the Boruta algorithm, the recursive feature elimination algorithm, and the overall importance score. Then, considering all and the most important features, estimation was made using simple linear regression, support vector regression, decision trees, random forests, boosting, gradient boosting machine, and bagging and stacking algorithms. The findings indicate that variables such as the number of traffic accidents, number of teachers, number of academics, number of hospitals, and number of housing sales are among the prominent determinants of both incoming and outgoing migration. Moreover, the application of variable selection significantly reduced prediction errors, and ensemble learning algorithms—particularly stacking—achieved notably high performance.

Bu çalışmada, 2018-2022 yılları arasında Türkiye’de il bazında iç göçü etkileyen değişkenler değişken önemi ile belirlenmiş ve makine öğrenmesi algoritmaları ile göç tahmini yapılmıştır. Alınan göç ve verilen göç ayrı ayrı ele alınmıştır. Çalışmanın temel amacı, alınan ve verilen göçü etkileyen faktörleri ayrıntılı biçimde belirlemek ve tahminleme sürecinde hangi değişkenlerin daha açıklayıcı olduğunu ortaya koymaktır. Bu yönüyle çalışma, Türkiye’de iç göçe yönelik makine öğrenmesi yaklaşımıyla gerçekleştirilen nadir örneklerden biri olup, alana özgün katkılar sunmaktadır. Yapılan çalışmada 2018-2022 yılları arasında il bazında erişilebilen ve literatürde sıklıkla kullanılan: akademisyen sayısı, hastane sayısı, özel hastane sayısı, GSYİH, öğretmen sayısı, okul sayısı, tarım alanı, nüfus yoğunluğu, nüfus artış hızı, muhtemel eğitim süresi, ortalama eğitim süresi, trafik kaza sayısı, otomobil sayısı, traktör sayısı, bitirilen eğitim durumu, ithalat, ihracat, hekim sayısı, hastane yatak sayısı ve konut satış sayısı değişkenleri alınmıştır. R programında; Caret paketi ile çeşitli modelleme teknikleri, Boruta algoritması, Özyinelemeli Özellik Eleme algoritması ve Ortak önem skoru kullanılarak değişken önemi belirleme işlemi gerçekleştirilmiştir. Daha sonra tüm değişkenler ve en önemli değişkenler dikkate alınarak; basit doğrusal regresyon, Destek Vektör Regresyonu, Karar Ağaçları, Rassal Ormanlar, Güçlendirme, Gradyan Artırma Makinesi, Çantalama ve Yığınlama algoritmaları kullanılarak tahmin yapılmıştır. Elde edilen sonuçlara göre, özellikle trafik kaza sayısı, öğretmen sayısı, akademisyen sayısı, hastane sayısı ve konut satış sayısı gibi değişkenler hem alınan hem de verilen göçte öne çıkan belirleyiciler arasında yer almıştır. Ayrıca, değişken seçimi sonrası yapılan modellemelerin hata düzeylerini düşürdüğü ve özellikle topluluk öğrenmesi algoritmalarının (örneğin stacking) yüksek başarı sağladığı görülmüştür.
Türkiye’de İllere Göre İç Göçe İlişkin Makine Öğrenmesi Yöntemleri ile Değişken Önemi ve Göç Tahmini
Keywords: Policy and Administration (Other); Politika ve Yönetim (Diğer)